Development of Low-Cost Growing Media with Mungbean as A Source of Carbon for Spirulina - Thathsatani, AOT (2023)
Spirulina is a multicellular, photosynthesis, filamentous blue-green algae which is found naturally in a wide range of fresh, marine, and brackish waters. It is an excellent source of protein, vitamins, minerals, lipids, carbohydrates, and pigments thus considered as the “superfood” of the century. The commercial production of Spirulina depends on many factors such as nutrient availability, temperature, and light. Zarrouk’s medium is known to be the standard media (SM) which contains all the macro and micro-nutrients required for the growth of Spirulina. The cost of nutrients is however found to be the second limiting factor next to labor cost affecting the commercial-scale production of Spirulina. The cost of carbon source is higher than that of N and P sources. Therefore, this study aimed at developing a low-cost medium for large-scale production of Spirulina. This intention was implemented by substituting carbon sources present in SM with cheaper and locally available carbon sources. Two separate experiments were conducted using a complete randomized design (CRD) with 3 replicates. The conventional carbon source in Zarrouk’s medium (NaHCO3) was substituted with low-cost carbon sources i.e., Mungbean flour (before and after germination separately). The carbon content in SM was replaced by 100 %, 75 %, 50 % and 25 % of Mungbean flour. Zarrouk’s medium was used as the control. The culture was maintained at 30 0C ± 2 0C under 4000 Lux, continuous illumination using a white, fluorescent tube for 16 days. Growth was measured using a spectrometer and optical density (OD) values were recorded at 560 nm with two days interval. Data were analyzed using SAS version 9.4.  The best growth of Spirulina was recorded at the 50 % replacement of carbon in SM by Mungbean flour (before germination). Mungbean flour (after germination) could also replace 25 % of carbon in Zarrouk’s media. Taking the cost factor into consideration, 50 % replacement of carbon in Zarrouk’s medium by Mungbean flour (before germination) can be recommended for commercial scale cultivation. The comparative cost reduction of this replacement is estimated to be 50 %.